2021
DOI: 10.1111/jocn.15753
|View full text |Cite
|
Sign up to set email alerts
|

Dispatched nurses’ experience of wearing full gear personal protective equipment to care for COVID‐19 patients in China—A descriptive qualitative study

Abstract: Aims and objectives:We explored dispatched nurses' experiences of wearing full gear personal protective equipment to care for patients with coronavirus disease-2019 in Wuhan, China.Background: Full gear personal protective equipment is the primary and foremost measure to prevent the contact and transmission of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV2); however, working in full gear personal protective equipment may hinder nursing care activities and thus negatively affect patients' and nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Referring to their experiences from past pandemics, like Ebola and MERS, and from today’s COVID-19, many healthcare professionals have reported difficulties with PPE use (Bambi et al, 2020 ; Kang et al, 2018 ; Liu et al, 2020 ; Lucchini, et al, 2020a ; Sun et al, 2020 ). In addition to these difficulties related to PPE use, there have also been problems procuring enough quality PPEs to meet the growing demand in the fight against COVID-19 in both Turkey and across the world (Catton, 2020 ; Celik et al, 2020 ; Chen et al, 2021 ; Jackson et al, 2020 ). This is a major issue, considering that nurses must have the proper quality PPE to protect themselves when they are in physical contact with their patients and are responsible for providing them with effective care and helping them recover their health in the COVID-19 pandemic, which has proven to be a difficult crisis to control and manage.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to their experiences from past pandemics, like Ebola and MERS, and from today’s COVID-19, many healthcare professionals have reported difficulties with PPE use (Bambi et al, 2020 ; Kang et al, 2018 ; Liu et al, 2020 ; Lucchini, et al, 2020a ; Sun et al, 2020 ). In addition to these difficulties related to PPE use, there have also been problems procuring enough quality PPEs to meet the growing demand in the fight against COVID-19 in both Turkey and across the world (Catton, 2020 ; Celik et al, 2020 ; Chen et al, 2021 ; Jackson et al, 2020 ). This is a major issue, considering that nurses must have the proper quality PPE to protect themselves when they are in physical contact with their patients and are responsible for providing them with effective care and helping them recover their health in the COVID-19 pandemic, which has proven to be a difficult crisis to control and manage.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous research on the experiences of non-OR healthcare personnel involved in the COVID-19 care ( 17 ). Working in protective gear has been described as challenging to other frontline healthcare personnel and as a contributor to increased work-related stress during the pandemic ( 18 ). Interestingly, the experiences of OR team members in the present study did, however, differ somewhat.…”
Section: Discussionmentioning
confidence: 99%
“…Chauhan, Mullan & Mistry [ 45 ] from India conducted a cross-sectional study among health care workers to determine the barriers for PPE use and reported that 53.2% of the nurses were agreed and 38.7% were strongly agreed that wearing PPE was causing discomfort during the nursing care activities of the COVID-19 patients. A descriptive qualitative study by Chen et al [ 46 ] from Wuhan, China explored the experiences of 15 nurses regarding to wearing full gear PPE and participants reported discomfort while caring activities and need help of their colleagues on occasion to complete their nursing cares. These results clarified the importance of comfortable PPE use in proper patient care.…”
Section: Discussionmentioning
confidence: 99%
“…According to a qualitative study from China that was conducted with nurses, headache was the most uncomfortable consequence of wearing PPE (e.g. N95 masks, goggles, face shields) due to the continuous pressure over the head, and nurses were concerned that if the bands or belts were so tight, they would suffer from a headache [ 46 ]. Similarly, in a cross-sectional study conducted with 158 healthcare professionals in Singapore, Ong et al [ 15 ] reported a correlation between using PPE and increased headache among healthcare workers who used PPE (N95 mask and eyewear) for more than 4 hours per day in the pandemic wards, emergency rooms and intensive care units.…”
Section: Discussionmentioning
confidence: 99%